Survey of Heteronormative Attitudes and Tolerance Toward Gender Non-conformity in Mountain West Undergraduate Students - Duncan, Steven G.; Aguilar, Gabrielle; Jensen, Cole G.; Magnusson, Brianna M. (Frontiers in Psychology, 2019)
Introduction: Heteronormative attitudes are prevalent in the U.S. and may contribute to discrimination against individuals who do not conform to traditional gender roles. Understanding the attitudes of undergraduate students is of particular interest as they may represent emergent societal views toward gender nonconformity. Methods: We conducted an online survey of Mountain West college students between the ages of 18-24 years to assess perceptions of personal gender conformity using the Traditional Masculinity-Femininity Scale (TMF), endorsement of heteronormative beliefs using the Heteronormative Attitudes and Beliefs Scale (HABS), and explicit tolerance of gender nonconformity on a 7-point Likert Scale. Results: The sample (n = 502) was 84% female and 78% white. Approximately 21% of respondents identified as a sexual minority and 36% identified as liberal or somewhat liberal (27% were conservative). The mean score on the TMF was 5.23 (95% CI: 5.15-5.32), indicating moderate levels of personal gender conformity. The mean HABS scores was 3.31 (95% CI: 3.19-3.43), indicating relatively low endorsement of heteronormative attitudes. TMF and HABS scores were both highest in heterosexual males. Most respondents (73%) were taught traditional gender roles in their childhood home, and 89% had heard negative opinions about nonconformity. The majority (80.6%) of respondents reported that they know someone who displays nonconforming characteristics and 61% said that they associate gender nonconformity with homosexuality. Approximately, 7% reported they had bullied others for not conforming to their gender. Among heterosexuals, 13.6% reported they had been bullied for gender nonconformity as did 42.7% of LGBTQ-identified individuals. Nearly 1-in-4 (23.6%) believed that male cross-dressing is wrong. Nearly 1-in-5 (17.2%) agreed with the statement that those who dress or act like the opposite sex were more likely to be abused or neglected during their development. Conclusion: Students reported relatively low endorsement of heteronormative attitudes and moderate levels of acceptance toward gender nonconforming persons. The sample reflects shifting attitudes when compared with outside data sets.